STRUKTUR KEPRIBADIAN TOKOH UTAMA DALAM FILM ANDAI IBU TIDAK MENIKAH DENGAN AYAH AKIBAT KONDISI FATHERLESS: KAJIAN PSIKOLOGI SASTRA - Kritsta Nola Syahfira; Untung Ritonga, Mara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the fatherless phenomenon in Indonesia, which affects children's psychological development but has yet to be examined psychoanalytically within the context of literary studies. This study aims to describe the personality structure of the character Alin comprising the Id, Ego, and Superego and to identify the ego defense mechanisms actualized by Alin in the film Andai Ibu Tidak Menikah dengan Ayah as a result of the fatherless condition. The study employs a qualitative descriptive-analytical approach grounded in Sigmund Freud's psychoanalytic theory. Data were collected through an audiovisual observation-and-notation technique applied to 40 scenes and dialogues involving Alin, and subsequently analyzed using narrative analysis. The findings indicate that the fatherless condition affects Alin's personality structure in an unbalanced manner: the Id component is highly dominant, marked by father hunger, impulsive drives, and emotional outbursts; the Superego develops in an overly punitive direction; while the Ego weakens yet remains functionally present in limited ways. All six ego defense mechanisms are identified in Alin: repression and denial as the dominant mechanisms, increasingly infantile regression under mounting pressure, projection that disrupts her capacity for trust in romantic relationships, rationalization as a logical cover for fear, and sublimation as the ultimate psychological resolution. These three dimensions operate as a single interconnected psychological system, with the fatherless condition as its root.